"They have their music and we have ours": The Political Woody Guthrie. Issue 3 (27th May 2019) - Carr, Nicholas
Abstract: In the last decade, scholars of American history and culture have begun to examine the political project of Woody Guthrie, who has now taken up his long-predicted place in a national cultural canon. This essay seeks to build on that literature by offering a reading of Guthrie's texts that is informed by radical theories as to the possibility and practice of cultural politics. It explores a political effort of considerable sophistication, which, when probed with Gramscian and other theoretical tools, brings out a radical strategy embedded in a vision of American culture and manifested in Guthrie's trademark themes: from the hobo to the war effort, from contemporary working life to the history of labor. His voluminous output provides a basis for discussion among scholars interested in the cross-over between radical theory and cultural politics, even as its subsequent history raises questions as to the possibilities of radical culture itself.